Gut Microbiota Manipulation in Mice Fed High or Low Glycemic Diets Affects Metabolic and Eye Health (P20-042-19). (13th June 2019) - Smith, Kelsey; Francisco, Sarah; Zhu, Ying; Barger, Kathryn; Smith, Donald E; Greenberg, Andrew; Taylor, Allen; Rowan, Sheldon
Abstract: Objectives: We sought to identify the role of gut microbiota in the previously discovered relationship between a high glycemic diet and the development of retinal damage and metabolic health outcomes in aged mice. Methods: Male C57Bl6/J mice aged 12 months were fed equal amounts of a high glycemic (HG) or low glycemic (LG) diet for 12 months. The compositions of the diets were identical apart from the starch, which was 100% amylopectin in the HG diet and 30% amylopectin/70% amylose in the LG diet. Within each diet, mice were assigned to one of three treatment conditions: antibiotic ablation of gut microbiota (HGabx or LGabx), weekly fecal microbiota transplants (FMT) from donor control mice fed the alternate diet (HG[tLG] or LG[tHG]), or a control group. Mice were weighed weekly and feces and urine were collected at regular intervals for microbiome and metabolome analysis respectively. Mice underwent MRIs to determine body composition, intraperitoneal glucose tolerance tests to determine glycemic responses, and eye fundus imaging and fluorescein angiography to evaluate the health of the retina and retinal vasculature. Results: Compared with LG-fed controls, the HG-fed controls had significantly increased body fat mass, decreased insulin sensitivity, and an increased prevalence of retinal damage including hypopigmentation and vascular tortuosity. There was no significant difference in body weight between the HGabx and LGabx group throughout the study. The LGabx group had a significantly higher body weight and the HGAbx had significantly lower body weight than their respective control groups throughout the study. The LGabx group had the highest prevalence of abnormal retinal findings. Survival was significantly decreased in the HGabx mice compared with mice of all other groups of mice, and most died suddenly and presented with an enlarged and hemorrhagic cecum. There was no significant effect of the FMT on body weight or body composition compared with the control mice. The HG[tLG] group had improved insulin sensitivity relative to the HG controls. Conclusions: Gut microbiota mediate the relationship between the glycemic response to the diet and health outcomes such as obesity, insulin sensitivity, eye health, and survival. Funding Sources: BrightFocus Foundation, USDA/NIFA AFRI grant 2015-05470, USDA contract 1950-510000-060-03A from ARS, Stanley N. Gershoff Scholarship.